2016
DOI: 10.1016/j.toxlet.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivity of metabolically competent and non-competent HepaRG cells to apoptosis induced by diclofenac combined or not with TNF-α

Abstract: The role of reactive metabolites and inflammatory stress has been largely evoked in idiosyncratic hepatotoxicity of diclofenac (DCF); however mechanisms remain poorly understood. We aimed to evaluate the influence of liver cell phenotype on the hepatotoxicity of DCF combined or not with TNF-α using differentiated and undifferentiated HepaRG cells, and for comparison, HepG2 cells. Our results demonstrate that after a 24h-treatment metabolizing HepaRG cells were less sensitive to DCF than their undifferentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 53 publications
2
14
1
Order By: Relevance
“…DCF induces adverse reactions in some patients (Boelsterli, 2003). Involvement of oxidative stress enzymes and drug metabolizing enzymes in this toxicity was reported in in vitro hepatic and non-hepatic models (Al-Attrache et al, 2016;Fredriksson et al, 2011;van Leeuwen et al, 2011c). DCF was reported to induce oxidative stress, apoptosis, cholestasis by diverse mechanisms (Al-Attrache et al, 2016;Fredriksson et al, 2011;Fredriksson et al, 2014;Maiuri et al, 2015) including deregulation of some ABC and SLC transporters (Al-Attrache et al, 2016), respiratory chain components and PKC signaling (van Leeuwen et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DCF induces adverse reactions in some patients (Boelsterli, 2003). Involvement of oxidative stress enzymes and drug metabolizing enzymes in this toxicity was reported in in vitro hepatic and non-hepatic models (Al-Attrache et al, 2016;Fredriksson et al, 2011;van Leeuwen et al, 2011c). DCF was reported to induce oxidative stress, apoptosis, cholestasis by diverse mechanisms (Al-Attrache et al, 2016;Fredriksson et al, 2011;Fredriksson et al, 2014;Maiuri et al, 2015) including deregulation of some ABC and SLC transporters (Al-Attrache et al, 2016), respiratory chain components and PKC signaling (van Leeuwen et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…DCF adverse effects have been related to different factors including its metabolism into 4′-OH-DCF, 5-OH-DCF, and acyl glucuronides (Bort et al, 1999;Kretz-Rommel and Boelsterli, 1993;Wang et al, 2004). We recently demonstrated that DCF-induced toxicity in hepatic HepaRG cell lines decreases as the cells differentiate and express DCF-metabolizing and detoxifying enzymes (Al-Attrache et al, 2016). An opposite effect was reported in Saccharomyces cerevisiae where heterologous expression of DCF-metabolizing cytochrome P450 potentiates DCF toxicity and reactive oxygen species (ROS) generation (van Leeuwen et al, 2011c).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…IL-6 and IL-1β but not TNF-α aggravated BC dilatation caused by all cholestatic ATBs in HepaRG hepatocytes. Noticeably, TNF-α was also found to be ineffective on diclofenac-induced BC deformation (Al-Attrache et al, 2016). Importantly, cytokine effects were evaluated in a medium containing 2% bovine serum (i.e.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…At concentrations that have been widely used in in vitro studies, i.e. TNF-α (10 ng/ml), IL-6 (5 ng/ml) and IL-1β (0.5 ng/ml)(Al-Attrache et al, 2016;Bachour-El Azzi et al, 2014;Rubin et al, 2015), none of these cytokines caused any cytotoxicity, as evaluated by caspase-3 activity and MTT assays after 2 daily repeated additions.…”
mentioning
confidence: 99%